Environmental, Social, and Governance Performance and Stock Returns: Empirical Evidence on the Value Relevance of Sustainability Disclosure - Rossalina, Ni Luh Ade Meina; Sukartha, P. D'Yan Yaniartha; Ni Ketut Rasmini (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study investigates the relationship between environmental, social, and governance (ESG) performance both at the aggregate level and across its individual pillars and stock returns of firms listed on the Indonesia Stock Exchange over the 2019–2023 period. The research population comprises all publicly traded companies, with a final sample of 3,952 firm-year observations selected using a purposive sampling method. Data were sourced from Refinitiv Eikon and complemented with information from company financial statements. To assess the relationship between ESG performance and market outcomes, multiple linear regression analysis was employed. The empirical findings reveal a negative association between overall ESG performance and stock returns, a pattern that also holds for each of the ESG dimensions individually (environmental, social, and governance).